Ten outstanding campus journalists of La Salle - Ang Pahayagang Plaridel-De La Salle University, Manila (Animo Repository, 1994)
Ten outstanding campus journalists of La Salle were honored as the first recipients of the Gawad Efren Abueg Para sa Pampahayagang Pangkampus, as part of the celebration of the 10th anniversary of Ang Pahayagang Plaridel, dubbed Plaridel: Isang Dekada.